Body Mass Index and Cholesterol and Uric Acid Levels in Diabetes: Indeks Massa Tubuh dan Kadar Kolesterol serta Asam Urat pada Penderita Diabetes - Aulia, Faradila Nur; Mushlih, Miftahul (Indonesian Journal on Health Science and Medicine, 2025)
General Background: Diabetes mellitus (DM) is a chronic metabolic disorder affecting millions worldwide, often linked to impaired insulin secretion or function. Specific Background: Dyslipidemia and hyperuricemia are frequent metabolic disturbances in DM, and body mass index (BMI) is commonly used to assess nutritional status, yet its role in predicting cholesterol and uric acid levels among DM patients remains unclear. Knowledge Gap: While previous studies suggest possible associations, evidence on whether BMI significantly correlates with cholesterol and uric acid in DM is inconsistent. Aim: This study investigated the relationship between BMI and cholesterol and uric acid levels in DM patients. Results: A cross-sectional study of 30 respondents at Anna Medika Madura General Hospital used CHOD-PAP and Uricase-PAP methods, showing cholesterol levels ranging 136–278 mg/dl, uric acid 3.4–12.1 mg/dl, and BMI 18.0–34.5 kg/m². Statistical analysis (Chi-square, p > 0.05) indicated no significant association between BMI and cholesterol or uric acid. Novelty: This study emphasizes that BMI alone is insufficient to predict lipid and uric acid abnormalities in DM patients. Implications: Findings highlight the need for comprehensive metabolic assessment beyond BMI for effective DM management. Highlights: No significant link between BMI and cholesterol or uric acid in DM. BMI values ranged from normal to obese, but metabolic changes varied. Clinical monitoring of DM requires broader parameters beyond BMI. Keywords: Diabetes Mellitus, Body Mass Index, Cholesterol, Uric Acid, Cross-Sectional Study